A Study of Human Resource Development in the Quasi-Governmental Organizations: Evidence from Aceh, Indonesia - Taufik, Taufik; Setiyono, Budi; Kismartini, Kismartini; Astuti, Retno Sunu (International Journal of Advances in Social Sciences and Humanities, 2023)
Today, Effective human resource management impacts an organisation's success. A proper plan is required to obtain quality human resources and avoid the conventional norm. This study aims to analyse the practice of human resource capacity building in Aceh's Ulama Consultative Council (MPU) as a semi-governmental institution. This study applies a qualitative-descriptive approach using data collection techniques, including in-depth interviews, field observations, and documentation, such as official reports, scientific literature, journals, and other sources. The study showed that Aceh’s MPU needs to improve its human resources development method. In creating top-notch, impartial, and high-integrity human resources, it is vital to change the selection process for Aceh’s MPU members. There are many ways to improve natural selection based on the popular vote. If their voices are raised, members with high competence and integrity will be chosen for office. This issue can be resolved if the recruiting procedure is handled by experts (agencies) to create objectivity when choosing MPU Aceh members.